Analisis Pertumbuhan Ekonomi Dalam Peradaban Islam: Studi Kasus Pada Zaman Ke Khalifahan Abbasiyah - Silalahi, Annisyah Nur; Ayu, Dia Fajar; Dalimunthe, Faisal Anwar; Zein, Ahmad Wahyudi (STAI Denpasar Bali, 2025)
This study aims to examine economic growth during the Abbasid Caliphate and to identify Islamic economic principles that can be adapted to a modern context. Through this study, it is hoped that a more inclusive and equitable economic model can be found. This research employs a literature review method, gathering data from various sources, including historical texts, scientific articles, and economic reports. This approach enables the researchers to comprehensively explore the economic dynamics of the Abbasid era.The study reveals that during the Abbasid period, economic growth was achieved through innovative policies, such as infrastructure development and transparent financial management via the Baitul Mal. The trade sector expanded rapidly with Baghdad as a global trade hub, while fair taxation policies and support for knowledge advancement further strengthened economic stability. The application of Islamic principles, such as social justice and wealth distribution, played a crucial role in creating an inclusive and sustainable economy.